Advances and Prospects in Antibacterial-Osteogenic Multifunctional Dental Implant Surface - Wang, Zixuan; Li, Baosheng; Cai, Qing; Li, Xiaoyu; Yin, Zhaoyi; Li, Birong; Li, Zhen; Meng, Weiyan (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, dental implantation has become the preferred protocol for restoring dentition defects. Being the direct contact between implant and bone interface, osseointegration is the basis for implant exerting physiological functions. Nevertheless, biological complications such as insufficient bone volume, poor osseointegration, and postoperative infection can lead to implant failure. Emerging antibacterial-osteogenic multifunctional implant surfaces were designed to make up for these shortcomings both during the stage of forming osseointegration and in the long term of supporting the superstructure. In this mini-review, we summarized the recent antibacterial-osteogenic modifications of the dental implant surface. The effects of these modifications on biological performance like soft tissue integration, bone osteogenesis, and immune response were discussed. In addition, the clinical findings and prospects of emerging antibacterial-osteogenic implant materials were also discussed.